Translation Techniques of English Dhammapada The Dear Ones into Indonesian Dhammapada Perasaan - Luh Sari Damayanti (Journal of Development Research, 2020)
Dhammapada English Source text is very famous among the Asian, Western and the European. We have the Indonesian Translation as the only one Translation admitted by Yayasan Abdi Dhamma Indonesia and the Source as Original English Text from Buddha Education Association Inc. There are 12 (twelve) poems in English of chapter XVI The Dear Ones and in Indonesian as Target Language with the same title of The Dear Ones as Perasaan; also in the same chapter XVI. The objective of this research is to determine the kinds of translation techniques used in The Dear Ones chapter XVI. The second objective is to determine that there is no deviation between the English The Dear Ones chapter XVI and the Indonesian Dhammapada Translation Text of Perasaan. This research method is using the qualitative approach since it is the suitable approach for this literature works. The result of this research is the used of Adaptation Technique Translation is dominating the translation text. The percentage of Adaptation technique is 57,6 %. The second is word for Word Translation Technique 35,2 % and the miscellaneous technique combination both Adaptation and Word for Word techniques 7,2%. There is definitely no deviation between English Original Source text and Indonesian Dhammapada as Target language. I hope that this research is useful and gives benefit for the researcher, the student, and the reader. Thankyou.